Avaliação do risco de colisão entre embarcações e baleias-jubarte (Megaptera novaeangliae) na costa brasileira - Portal, Caroline Santos (Universidade Federal de Juiz de Fora (UFJF), 2023)
The increase in the human use of the marine environment in the last several decades emphasizes the need for investigations on anthropogenic pressures to improve the conservation of marine megafauna. Ship strikes have become one of the greatest threats to cetaceans and an important source of mortality to whales in the present day. Efforts to understand the effects of this threat have been mostly focused on Northern Hemisphere species. In the South Atlantic, the potential impact of marine traffic remains poorly known. Here we used humpback whale (Megaptera novaeangliae; n=30) satellite monitoring and maritime traffic AIS data to estimate the collision risk at the central coast of Brazil between 2016 and 2019. A state-space model was used to account for observation errors and to regularize telemetry data. Residence time and proportion of time spent at the surface (i.e. the upper 10m layer of the water column) by whales, combined with fleet-specific vessel density, were used as proxies to estimate the relative probability of vessels encountering whales available to a collision in grid cells of ~8x8 km. We also identified areas where potential encounters were likely to inflict lethal injuries on humpback whales based on vessel length and speed. The cargo fleet was the most densely distributed and along with the tanker fleet, represented a great concern to humpback whales in Brazil. A higher risk of collision risk was recorded along the continental shelf, on the Abrolhos Bank – the main breeding ground for this population – and off the coasts of Rio de Janeiro and Espírito Santo states, an intense shipping traffic area with busy ports. By incorporating comprehensive whale- and vessel-related information, this study highlights the importance of spatially explicit risk assessments to conserve humpback whales in Brazil. O crescente uso humano no ambiente marinho nas últimas décadas, enfatiza a necessidade de investigar as pressões antrópicas para melhorar a conservação da megafauna marinha. As colisões com navios ...